Comparison of Drug Resistance of Helicobacter pylori Between Children and Adults in Jilin, China - Wang, Libo; Zhang, Jianguang; Hu, Meilian; Pang, Xiaoli (Turkish Journal of Gastroenterology, 2021)
Background: The drug resistance of Helicobacter pylori in children is gaining more and more attention. Methods: Polymerase chain reaction-reverse dot blot was used to analyze main virulence genes and drug resistance of H. pylori. Results: (1) The main H. pylori vacA virulence genotypes were s1/m1 and s1/m2 in Jilin, China. There was no significant difference in H. pylori virulence genotypes between children and adults. (2) The resistance rates of H. pylori to clarithromycin, metronidazole, and levofloxacin were high, the resistance rate to tetracycline and amoxicillin were relatively low. The drug-resistance rate of clarithromycin in children was significantly higher than that in adults. The single drug-resistance rate of metronidazole in adults was significantly higher than that in children. (3) The mutation sites of clarithromycin resistance in H. pylori were mainly A2143G of 23S rRNA gene, G616A of rdxA gene in metronidazole, N81K and D91G/N/Y of gyrA gene in levofloxacin, T556S and N562D/Y of PBP1 gene in amoxicillin, AGA926-928TTC and AG926-927GT of 16S rRNA gene in tetracycline. There was significant difference in D91Y of gyrA gene in levofloxacin between children and adults. (4) In different groups, the drug-resistance rate of clarithromycin in male children was higher than that in male adults. The drug-resistance rate of clarithromycin in children with peptic ulcers was higher than that in adults. Conclusion: There are some differences in drug resistance of H. pylori between children and adults, which indicated us to pay attention to the infection of H. pylori in children.